An aircraft seat discomfort scale using item response theory. (May 2019) - Menegon, Lizandra da Silva; Vincenzi, Silvana Ligia; Andrade, Dalton Francisco de; Barbetta, Pedro Alberto; Vink, Peter; Merino, Eugenio Andrés Díaz
Abstract: The purpose of this study is to construct an aircraft seat discomfort scale and verify the evidence of its validity and reliability. We developed a questionnaire and presented it to 1500 Brazilian passengers at an airport. The data analysis included: 1) factor analysis; 2) the analysis of the items to be used in the scale created using Item Response Theory. The scale covered all levels, from "without discomfort" to "maximum discomfort". At the level of minimal, a passenger feels that the aircraft seat is cramped and has little space. Discomfort tends to increase when passengers are unable to perform desired activities (eg: reading, sleeping), which causes irritation and disappointment. The maximum discomfort level occurs when noise disrupts activities and an aircraft seat is considered hard. The scale developed presented indications that it is reliable and valid, proving to be a useful tool for identifying levels of discomfort in aircraft seats. Highlights: Scale on aircraft seat discomfort shows evidences of validity and reliability. Item Response Theory possible to create a scale with different levels of discomfort. Discomfort minimum occurs when there is a limitation of space in the seat. Maximum discomfort occurs when there is seat hardness and the presence of noise. Difficulty to able successfully conduct the desired activity generate discomfort.